2015
DOI: 10.1080/00150193.2015.995007
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and Mossbauer Studies of Pb(Fe1/2Ta1/2)O3Multiferroic Ceramics Sintered from Mechanoactivated Powders

Abstract: The effect of high-energy mechanical activation on dielectric and magnetic properties of PbFe 1/2 Ta 1/2 O 3 (PFT) multiferroic was studied. M€ ossbauer studies have shown that the Neel temperature T N of the antiferromagnetic phase transition in PFT powders can be changed substantially by mechanical activation and subsequent annealing. The increase of T N by more than 70 K, as compared to PFT single crystal, was achieved in the mechanically activated PFT powder annealed at 700 C. Dielectric studies have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…As shown in Table 1, values for the fit parameters from the literature are scattered. Gusev et al [42] also reported that one of their samples had a difference of not more than 0.5 K for T m measured in the range 10 3 –10 6  Hz, which is very close to being independent of frequency. The absence of a unique Vogel–Fulcher parameterisation is presumed to reflect differences between samples arising from different methods of synthesis, such as grain size and B-site cation order.…”
Section: Pftmentioning
confidence: 66%
See 3 more Smart Citations
“…As shown in Table 1, values for the fit parameters from the literature are scattered. Gusev et al [42] also reported that one of their samples had a difference of not more than 0.5 K for T m measured in the range 10 3 –10 6  Hz, which is very close to being independent of frequency. The absence of a unique Vogel–Fulcher parameterisation is presumed to reflect differences between samples arising from different methods of synthesis, such as grain size and B-site cation order.…”
Section: Pftmentioning
confidence: 66%
“…Relaxor character for PFT is revealed by a broad maximum in the dielectric constant at a temperature, T m , in the vicinity of 250 K which varies with frequency in both pure and Li-doped samples [18, 19, 28, 3142]. This dispersion is described using the Vogel–Fulcher representation of freezing behaviour where ν is the measurement frequency for a given value of T m , ν o is an attempt frequency, E a is an activation energy, k B is the Boltzmann constant and T VF is the zero frequency freezing temperature.…”
Section: Pftmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the fundamental coupling mechanism between electric and magnetic order parameters has been the hottest topic of research in the present scenario [2,3] (PFT) are the promising candidates and exhibit extraordinary dielectric constant with diffuse kind of ferroelectric phase transition [4,5].…”
Section: Introductionmentioning
confidence: 99%